Blood loss and related laboratory changes after single-event multilevel surgery and hip reconstructive surgery in patients with cerebral palsy - Min, Jae Jung; Kwon, Soon Sun; Kim, Kyu Tae; Sung, Ki Hyuk; Lee, Kyoung Min; Choi, Young; Park, Moon Seok (CiOS Clinics in Orthopedic Surgery, 2021)
Background: Single-event multilevel surgery (SEMLS) and hip reconstructive surgery (HRS) often cause intraoperative bleeding, consequently increasing the probability of transfusion and postoperative laboratory changes. Therefore, it is important to assess risk factors to predict the amount of blood loss. This study aimed to evaluate blood loss, its influencing factors, and the related laboratory changes during SEMLS and HRS in patients with cerebral palsy (CP). Methods: We retrospectively examined consecutive CP patients who underwent SEMLS and HRS. Surrogate markers of blood loss, including preoperative and postoperative hemoglobin (Hb), hematocrit, and changes in Hb concentration, were assessed. Albumin, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and creatine levels were also analyzed for related laboratory changes. Risk factors were analyzed using multiple regression and logistic regression models. Results: The overall cohort comprised 1,188 patients. Of them, 1,007 and 181 underwent SEMLS and HRS, respectively. Fur-thermore, 72 of 181 patients underwent a concomitant Dega osteotomy. The regression model showed that low preoperative Hb concentration (p < 0.001), high albumin level (p = 0.007), low body mass index (BMI) (p = 0.002), and bilateral HRS (p < 0.001) were significant risk factors of postoperative anemia. Valproate medication was associated with Hb drop, and the risk factors for Hb level < 8 g/dL on postoperative day 2 were bilateral HRS and Dega osteotomy in the HRS subgroup. In total, 21.6% had elevated AST levels on postoperative day 2, and bilateral HRS (p < 0.001), Gross Motor Function Classification System (GMFCS) level V (p = 0.041), Dega osteotomy (p < 0.001), and high preoperative AST level (p < 0.001) increased the risk of AST elevation. Conclusions: We have summarized the estimated blood loss and related laboratory changes after SEMLS and HRS in patients with CP and identified the risk factors. Clinical guidelines should be accordingly developed to include assessment of these risk factors and their impact in the outcomes of CP patients undergoing SEMLS and HRS.
Keywords: Adolescent; Biomarkers; Blood Loss, Surgical; Cerebral Palsy; Child; Female; Hip Joint; Humans; Male; Reconstructive Surgical Procedures; Retrospective Studies; Risk Factors; Blood loss; Cerebral palsy; Hip reconstructive surgery; Single event multilevel surgery